Effects of freeze-drying and vacuum-drying on the quality, total phenolic contents, and antioxidant activities of bee honey in northern Thailand - Rossaporn Jiamjariyatam; Orachorn Mekkerdchoo; Pakkapong Phucharoenrak; Lu Zheng (My University, 2024)
We aimed to evaluate the effect of freeze-drying and vacuum-drying on moisture, water activities (aw), total soluble solid (TSS), hydroxymethylfurfural (HMF), diastase activity, total phenolic content (TPCs), and antioxidant activities (ABTS, DPPH, FRAP, ORAC) of longan (Dimocarpus longan Lour.) blossom honey and Siam weed (Chromolaena odorata Lour.) honey. The fresh longan blossom honey and Siam weed honey were collected from a local apiarist in Northern Thailand. Freeze-drying at 0.013 kPa, −54℃ for 72 h or vacuum-drying at 2.5 kPa at 60 ℃ for 12 h was applied to dehydrate fresh honey. The moisture of freeze-dried samples was 10.10% for longan blossom honey and 11.50% for Siam weed honey, and the aw of both freeze-dried honeys was 0.43. Freeze- and vacuum-dried produced more TSS than fresh honey did (p ≤ 0.05). However, the amounts of TSS derived freeze-dry and vacuum-dry were not significantly different. Freeze-dried honey contained the highest HMF and the lowest diastase activity regardless of honey origins (p ≤ 0.05). Drying processes significantly increased the TPCs levels of honey (approximately 2 folds by freeze-drying method). The antioxidant activity of dried honey was significantly higher than that of fresh honey. It was observed that the freeze-drying method tended to better preserve the antioxidant activity of honey compared to vacuum-drying methods in both types of honey. The results indicated that drying processes significantly affect the quality of dried honey, including TSS, HMF, diastase activity, TPCs, and antioxidant activity. In this study, freeze-drying emerged as the relatively low temperature drying method that can preserve the quality of honey, especially in terms of TPCs and antioxidant activity.
Keywords: Vacuum drying; Bee Products Chemical Analysis